Peirce, Wittgenstein y Davidson: coincidencias anti-escépticas - Kalpokas, Daniel (2008)
“Peirce, Wittgenstein and Davidson: Anti-skeptic Coincidences”. This paper shows some similarities among Peirce’s, Wittgenstein’s and Davidson’s answers to skepticism. In each case, the response to Cartesian skepticism consist in pointing out the contradictory character of the skeptical doubt in itself.More specifically, those philosophers agree on the following points: (i) in order to face the challenge of skepticism we have to examine its bases without conceding the terms of the challenge; (ii) the skeptic cannot doubt without assuming some propositional contents as true. In this sense, the skeptic commits performative contradiction; (iii) in his challenge, the skeptic omits the practical dimension of language and knowledge. That is the source of his difficulties.